Assessment of QT Interval and QT Dispersion Following Stellate Ganglion Block Using Computerized Measurements. Issue 6 (1st November 2001) - Egawa, Hirotoshi; Okuda, Yasuhisa; Kitajima, Toshimitsu; Minami, Junichi
Abstract : Background and Objectives: Prolongation of QT interval and QT dispersion (QTD) may be associated with an increased risk of arrhythmias. This study was designed to investigate the effects of right or left stellate ganglion block (SGB) on RR interval, QT interval, the rate-corrected QT (QTc) interval, QTD and the rate-corrected QTD (QTcD) using computerized measurements. Methods: Ten healthy volunteers underwent both right and left SGBs using 7 mL 1% mepivacaine with a 7-day interval between the 2 blocks. The measurement from the 12-lead electrocardiogram was performed for 60 minutes after SGB. Results: Right SGB induced a significant decrease of RR interval immediately after the block, and significant increases of QT interval, QTc interval, QTD, and QTcD from immediately through 50 minutes after the block ( P < .01). Left SGB induced a significant decrease of RR interval, and significant increases of QTc interval and QTD immediately after the block ( P < .01). Left SGB also produced a significant decrease of QT interval from 20 through 50 minutes after the block, and a significant decrease of QTc interval from 30 through 50 minutes after the block ( P < .05). Conclusions: Right SGB induces increases of the QT interval, QTc interval, QTD, and QTcD, and left SGB induces decreases of the QT interval and QTc interval.